Women, Educational Leadership and Societal Culture - Saeeda Shah; Umbreen Shah (MDPI AG, 2012)
This paper argues that women's participation in the public and their access to senior leadership positions is defined by cultural and belief systems in a society. It draws upon a study of Women College heads of women-only colleges, in a region in Pakistan, to unveil the discursive dynamics in that societal context where complex factors interact to determine what is acceptable in that culture. This has implications for women' roles and determines their practices as college heads. The study also unveiled the culturally-informed strategies adopted by these women professionals to exercise their role as college heads in the presence of multiple cultural constraints.